Efficacy of Nirmatrelvir tablet/Ritonavir tablet in patients infected with COVID-19 aged 90 years and older - WEI Xueman; ZHANG Jingxiang; LIU Tan (Shanghai yufang yixue)
ObjectiveTo study the effect and efficacy of Nirmatrelvir tablet/Ritonavir tablet in the treatment of patients with COVID‑19 infection aged ≥90 years, to inform pharmacological treatment of patients aged ≥90 years with COVID‑19 infection.MethodsMild to moderate COVID-19 patients who were hospitalized in the Department of Geriatrics of the First Affiliated Hospital of the Naval Medical University from March 2022 to June 2024, aged ≥90 years, and who had not been vaccinated against novel coronavirus were selected as the research subjects. A total of 112 patients who received Nirmatrelvir tablet/Ritonavir tablet antiviral treatment within 5 days after the diagnosis of COVID‑19 infection were referred to the drug group, and 80 patients who were not treated with antiviral drugs were referred to as the control group. A retrospective research method was employed to gather and compare patitents’ clinical laboratory data before and after antiviral treatment, such as blood routine tests, inflammatory markers, coagulation function tests, liver and renal function tests, electrolyte levels, and blood gas analysis, between the drug group and the control group. Additionally, the time duration to negative conversion and 28-day all-cause mortality rates were compared between the two groups. Logistic regression analysis was conducted on factors associated with mortality, such as the oxyhemoglobin saturation after treatment, time duration to negative conversion, and the use of Nirmatrelvir tablet/Ritonavir tablet or not, while correlation analysis was performed to evaluate the efficacy of Nirmatrelvir tablet/Ritonavir tablet based on the level of oxyhemoglobin saturation, time duration to negative conversion, and all-cause mortality rates within 28 days.ResultsAfter treatment, oxyhemoglobin saturation increased in the drug group (t=-2.726, P=0.011), and the differences between the indicators in the control group compared to the pre-treatment period were not statistically significant (all P>0.05). The time to negative conversion and 28-day all-cause mortality of control group were higher than those in the drug group (all P<0.05). Logistic regression analysis revealed that the lower the post-treatment oxyhemoglobin saturation, the lower the use of Nirmatrelvir tablet/Ritonavir tablet, the longer the time to conversion, and the higher the mortality rate of the patients (all P<0.05). Correlation analysis showed that treatment with Nirmatrelvir tablet/Ritonavir tablet resulted in higher oxyhemoglobin saturation (r=0.425, P=0.008), shorter time to negative conversion (r=-0.398, P=0.013), and lower all-cause mortality rates within 28 days (r=-0.370, P=0.022).ConclusionNirmatrelvir tablet/Ritonavir tablet is effective in mild and moderate infection patients aged ≥90 years who have not been vaccinated against COVID‑19 infection, and can increase patients’ oxyhemoglobin saturation, shorten the time to negative conversion, and reduce 28-day all-cause mortality rate.